Ethics of surgcial research in Tanzania (Tanzania Medical Journal, 2007)
Surgical procedures have often been introduced into practice without rigorous clinical research to check on safety and proof of cost-effectiveness as is done when researching on a new drug. This is because clinical research involves an inherent tension between the ethical values of pursuing rigorous science and protecting participants from harm. The latter may be particularly challenging when surgery is involved. However, clinical trials are unethical if they are not designed to answer valuable scientific questions with the use of valid research methods. In addition to having scientific merit, clinical trials must present a favorable risk–benefit ratio: the risks to participants must be minimized and justifiable by the benefits to them, if any, and the potential value of the scientific knowledge to be gained from the study. It is also essential that investigators obtain informed consent from participants and have an ethical responsibility to act in their best interest.A randomized, controlled clinical trial carried out in the surgical field, is not a form of individualized surgical therapy; it is a scientific tool for evaluating innovative procedures in groups of surgical research participants, with the aim of improving the care of similar patients in the future. Such clinical trials are not designed to promote the best interests of enrolled patients and may expose them to risks that are not outweighed by known potential benefits. Furthermore, the use of placebo (sham) surgery in controlled clinical trials has been controversial resulting in a lot of debate because the fundamental ethical principles of beneficence and non-maleficence appear to be violated. Patients could be exposed to complications of surgery with no prospects of possible benefits. It is therefore imperative that the use of placebo surgery must be evaluated in terms of the ethical principles appropriate to clinical research. As technology is expanding and health care resources becoming more limited, surgeons are compelled to evaluate surgical procedures and technology to ensure they are safe and effective.In conclusion, trials of surgical procedures including those involving the use of placebo surgery whenever required, should be conducted before new surgical procedures become standard treatments, provided that these trials meet the ethical requirements that are appropriate for clinical research. These ethical issues and requirements in surgical research and their relevance to a developing country like Tanzania is discussed in this paper. Keywords: Ethical, Surgical Research Tanzania Medical Journal Vol. 21 (1) 2006: pp. 28-31